2007
DOI: 10.1590/s2236-89062007000200009
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia de esporos de pteridófitas do Parque Estadual das Fontes do Ipiranga (São Paulo, Brasil): Família: 5-Dennstaedtiaceae

Abstract: -(Morphology of spores of pteridophyte from the "Parque Estadual das Fontes do Ipiranga" (São Paulo, Brazil): 5. Dennstaedtiaceae). Spores of eleven pteridophyte species of the family Dennstaedtiaceae from the "Parque Estadual das Fontes do Ipiranga" were studied. The family is represented in the area by five genera: Histiopteris, Hypolepis, Lindsaea, Pteridium and Saccoloma. Descriptions, illustrations, observations, as well as an identification key are presented. Key words: Dennstaedtiaceae, morfology, Pteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
0
1
2
Order By: Relevance
“…This would characterise Terpsichore as the only grammitid genus producing both types of spores. This feature was not confirmed by our study, but the production of both types of spores by the same specimen has been observed in other fern and lycophyte families such as the Vittariaceae (Lorscheitter et al, 1998) and Dennstaedtiaceae (Tryon & Lugardon, 1991;Esteves & Coelho, 2007). VR = variation range; X = mean; S x = standard mean deviation; S = sample standard deviation; CV = coefficient of variability at 95%; CI = confidence interval at 95%.…”
Section: Serpocaulon Adnatumcontrasting
confidence: 74%
“…This would characterise Terpsichore as the only grammitid genus producing both types of spores. This feature was not confirmed by our study, but the production of both types of spores by the same specimen has been observed in other fern and lycophyte families such as the Vittariaceae (Lorscheitter et al, 1998) and Dennstaedtiaceae (Tryon & Lugardon, 1991;Esteves & Coelho, 2007). VR = variation range; X = mean; S x = standard mean deviation; S = sample standard deviation; CV = coefficient of variability at 95%; CI = confidence interval at 95%.…”
Section: Serpocaulon Adnatumcontrasting
confidence: 74%
“…Este trabalho dá continuidade aos estudos morfológicos em esporos de pteridófitas do PEFI (Esteves & Coelho 2007) e dá suporte para a pesquisa sobre precipitação esporo-polínica e análise palinológica de sedimentos na área.…”
Section: Introductionunclassified
“…Respecto a la Provincia Fitogeográfica Paranaense, los únicos estudios palinológicos que mencionan especies de Dennstaedtiaceae son los de Lorscheitter et al (2002) en Rio Grande do Sul y Esteves & Coelho (2007) en São Paulo.…”
Section: Cicutariaunclassified